Diagnosis and surgical management of Herlyn-Werner-Wunderlich syndrome - Jennifer A. Munley; Janice A. Taylor (Elsevier, 2020)
Abdominal pain in the adolescent population is rarely attributed to anatomic variance. Minimal consideration placed on this pathology can present a diagnostic dilemma and delay in care if such options are not investigated. Our case report describes the workup, step-by-step imaging and multidisciplinary approach to a twelve-year-old female who presented with abdominal pain at an outside facility, where she was originally diagnosed with a pelvic mass seeming to arise from the left ovary on ultrasound. Subsequent CT at the authors' institution indicated a hydrometrocolpos and possible uterine and vaginal duplication; exam under anesthesia revealed uterine didelphys with obstructed left hemivagina. MRI confirmed the diagnosis of Herlyn-Werner-Wunderlich Syndrome and return to the operating room resulted in successful evacuation of the obstructed hemivagina by vaginal septum resection. Post-operatively, she is doing well, menstruating without difficulty, and has not had recurrence of symptoms. This case elucidates the need for consideration of Mullerian duct anomalies in female pediatric patients presenting with lower abdominal pain. Keywords: Uterine didelphys, Herlyn-Werner-Wunderlich syndrome, Obstructed hemivagina and ipsilateral renal anomaly (OHVIRA)